2015
DOI: 10.1007/s00438-015-1150-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole-transcriptome analysis of mouse adipose tissue in response to short-term caloric restriction

Abstract: Caloric restriction (CR) has been shown to extend the lifespan of many species by improving cellular function and organismal health. Additionally, fat reduction by CR may play an important role in lengthening lifespan and preventing severe age-related diseases. Interestingly, CR induced the greatest transcriptome change in the epididymal fat of mice in our study. In this transcriptome analysis, we identified and categorized 446 genes that correlated with CR level. We observed down-regulation of several signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 107 publications
3
11
0
Order By: Relevance
“…That the b3 adrenoreceptor agonist stimulation revealed no intrinsic defect in BAT in Fgf13 +/2 mice was unexpected in the context of multiple studies that reported differential expression of Fgf13 in adipose in response to high-fat feeding or starvation (21)(22)(23)(24)(25). We therefore investigated specifically whether Fgf13 in adipose contributed to the observed metabolic phenotypes.…”
Section: Loss Of Fgf13 Does Not Cause Obesity Through Effects On Adipmentioning
confidence: 89%
See 2 more Smart Citations
“…That the b3 adrenoreceptor agonist stimulation revealed no intrinsic defect in BAT in Fgf13 +/2 mice was unexpected in the context of multiple studies that reported differential expression of Fgf13 in adipose in response to high-fat feeding or starvation (21)(22)(23)(24)(25). We therefore investigated specifically whether Fgf13 in adipose contributed to the observed metabolic phenotypes.…”
Section: Loss Of Fgf13 Does Not Cause Obesity Through Effects On Adipmentioning
confidence: 89%
“…We and others have characterized Fgf13 effects on cardiac function (13,14,20,(39)(40)(41), neuronal migration during development (19), epileptogenesis (12), and ion channel trafficking and targeting in the axon initiation segment of cultured hippocampal neurons (42), yet gene ablation studies have not been employed to investigate roles for Fgf13 in metabolism, despite multiple studies reporting differential expression in adipose tissue in response to alterations in diet and in different obesogenic genetic backgrounds (21)(22)(23)(24)(25). To begin to investigate metabolic functions we generated a global Fgf13 knockout mouse model on a C57BL/6J background.…”
Section: Fgf13 +/2 Mice Exhibit Hyperactivity When Housed At 22°c Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with earlier studies, which typically included a single treatment level, we used graded CR treatment groups (but see also Nogueira et al ., 2012; Kim et al ., 2016). This design enabled us to show not only that there was an increasing number of SDE metabolites with increasing CR, but also that many of these metabolites, including L‐carnitine, S1P and taurocholic acid, were increasingly upregulated with increasing CR.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition plays a crucial role in regulating the growth and reproductive performance of farm animals. Energy homeostasis exerts a significant influence on animal health and body condition [1]. Positive energy balance results in increased leptin and insulin concentrations in the blood, which subsequently increased glucose uptake.…”
Section: Introductionmentioning
confidence: 99%